Intelligent Interactive Multimedia Systems and Services Proceedings of 2018 Conference - De Pietro, Giuseppe; Gallo, Luigi; Howlett, Robert J.; Jain, Lakhmi C.; Vlacic, Ljubo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume presents a series of carefully selected papers on the theme of Intelligent Interactive Multimedia Systems and Services (IIMSS-18), but also including contributions on Innovation in Medicine and Healthcare (InMed-18) and Smart Transportation Systems (STS-18). The papers were presented at the Smart Digital Futures 2018 multi-theme conference, which grouped the AMSTA, IDT, InMed, SEEL, STS and IIMSS conferences in one venue in Gold Coast, Australia in June 2018. IIMSS-18 included sessions on 'Cognitive Systems and Big Data Analytics', 'Data Processing and Secure Systems', 'Innovative Information Services for Advanced Knowledge Activity', 'Autonomous System' and ' Image Processing'. InMed-18 papers cover major areas of 'Digital Architecture for Internet of Things, Big data, Cloud and Mobile IT in Healthcare' and 'Advanced ICT for Medical and Healthcare'. STS-18 papers provide a comprehensive overview of various aspects of current research into intelligent transportation technology.
Big Data Security on Cloud Servers Using Data Fragmentation Technique and NoSQL database -- A Comparison of Character and Word Embeddings in Bidirectional LSTMs for POS Tagging in Italian -- Data Mining in Social Network -- A Vision for Open Healthcare Platform 2030 -- Interactive Liver Segmentation in CT Volumes Using Fully Convolutional Networks -- A Plug-In for Automating the Finite Element Modeling of Flatfoot -- Pricing of Shared-parking Lot: An Application of Hotelling Model -- Unlock a Bike, Unlock New York: A study of the New York Citi Bike System -- Modeling and Analysis of Crash Severity for Electric Bicycle -- Study on Macroscopical Layout Optimization Model of Large Passenger Transfer Hub Facilities Based on NSGA-Ⅱ -- Traffic impact analysis of Gold Coast Light Rail Stage 2 -- Initial Classification Algorithm for Pavement Distress Images Using Features Fusion.
Keywords: Computational intelligence; Artificial intelligence; Multimedia systems; Computational Intelligence; Artificial Intelligence; Multimedia Information Systems